Identification of the temperature- induced larvicidal efficacy of Agave angustifolia against Aedes, Culex and Anopheles larvae - Mithilesh eKajla; Kurchi eBhattacharya; Kurchi eBhattacharya; Kuldeep eGupta; Ujjwal eBanerjee; Ujjwal eBanerjee; Parik eKakani; Lalita eGupta; Sanjeev eKumar (Frontiers Media S.A., 2016)
Synthetic insecticides are generally employed to control the mosquito population. However, their injudicious over usage and non-biodegradability are associated with many adverse effects on the environment and mosquitoes. The application of environment-friendly mosquitocidals might be an alternate to overcome these issues. In this study, we found that organic or aqueous extracts of Agave angustifolia leaves exhibited a strong larvicidal activity (LD50 28.27 µg/ml) against Aedes aegypti, Culex quinquefasciatus and Anopheles stephensi larvae within a short exposure of 12h. The larvicidal activity of Agave angustifolia is inherited and independent of the plants vegetative growth. Interestingly, the plant larvicidal activity was observed exclusively during the summer season (April-August, when outside temperature is between 30oC to 50oC) and it was significantly reduced during winter season (December-February, when the outside temperature falls to ~4oC or lower). Thus, we hypothesized that the larvicidal components of Agave angustifolia might be induced by the manipulation of environmental temperature and should be resistant to the hot conditions. We found that the larvicidal activity of Agave angustifolia was induced when plants were maintained at 37oC in a semi-natural environment against the controls that were growing outside in cold weather. Pre-incubation of Agave angustifolia extract at 100oC for 1h killed 60% larvae in 12h, which gradually increased to 100% mortality after 24h. In addition, the dry powder formulation of Agave angustifolia, also displayed a strong larvicidal activity after a long shelf life. Together, these findings revealed that Agave angustifolia is an excellent source of temperature induced bioactive metabolites that may assist the preparedness for vector control programs competently.